Proteomic and metabolomic profiling of methicillin resistant versus methicillin sensitive Staphylococcus aureus using a simultaneous extraction protocol - Boucherabine, Syrine; Giddey, Alexander; Nassar, Rania; Al-Hroub, Hamza M.; Mohamed, Lobna; Harb, Mohammad; Soares, Nelson Cruz; Senok, Abiola (Frontiers in Microbiology, 2024)
Background: Understanding the biology of methicillin resistant Staphylococcus aureus (MRSA) is crucial to unlocking insights for new targets in our fight against this antimicrobial resistant priority pathogen. Although proteomics and metabolomic profiling offer the potential to elucidating such biological markers, reports of methodological approaches for carrying this out in S. aureus isolates remain limited.We describe the use of a dual-functionality methanol extraction method for the concurrent extraction of protein and metabolites from S. aureus and report on the comparative analysis of the proteomic and metabolomic profiles of MRSA versus methicillin sensitive S. aureus (MSSA).: Bacterial reference strains MRSA ATCC43300 and MSSA ATCC25923 were used . The conventional urea methodology was used for protein extraction and a methanol based method was used for concurrent proteins and metabolites extraction. Proteomic and metabolomic profiling was carried out using TimsTOF mass spectrometry. Data processing was carried out using the MaxQuant version 2.1.4.0 Results: This study represents the first report on the utilization of the methanol extraction method for concurrent protein and metabolite extraction in Gram positive bacteria. Our findings demonstrate good performance of the method for the dual extraction of proteins and metabolites from S. aureus with demonstration of reproducibility.Comparison of MRSA and MSSA strains revealed 407 proteins with significantly different expression levels. Enrichment analysis of those proteins revealed distinct pathways involved in fatty acid degradation, metabolism and betalactam resistance. Penicillin-binding protein PBP2a, the key determinant of MRSA resistance, exhibited distinct expression patterns in MRSA isolates. Metabolomic analysis identified 146 metabolites with only one exclusive to the MRSA. The enriched pathways identified were related to arginine metabolism and biosynthesis. Conclusion: Our findings demonstrate the effectiveness of the methanol-based dualextraction method, providing simultaneous insights into the proteomic and metabolomic landscapes of S. aureus strains. These findings demonstrate the utility of proteomic and metabolomic profiling for elucidating the biological basis of antimicrobial resistance.